Adaptation scenarios to climate change and its implications on the food sector in Malaysia / Ferdous Ahmed - Ferdous, Ahmed (2016)

(untitled)
Malaysia is experiencing an unusual combination of droughts and extreme rainfall as a result of on-going changes to the climate. These unusual events and their consequences are a cause of worry among Malaysian policymakers. Given that Malaysia is not agriculturally self-sufficient, the effects of climate change threaten its food security and constitutes a source of national and economic vulnerability. To mitigate its negative effects, policy measures have been introduced to reduce the likely overall climatic effects. However, there have yet to be sufficient consideration for food sustainability and a future adaptation policy. Therefore, this study develops a quantitative adaptive model named the Malaysian Integrated Climate and Economy (MICE) model based on the dynamic Computable General Equilibrium (CGE) modeling structure to examine food sustainability and its adaptation policy. Adopting MICE, following the top-down approach this study empirically examines food sustainability and its adaptation policy and assesses the vulnerability impacts of climate change in food security by prioritizing a 50 year scenario (2015- 2065). To date, no relevant study has been conducted in Malaysia that emphasizes the climate change adaptation policy option based on national accounts (input-output table 2005) to help direct adaptation cost and damage scenarios for the country‘s policy options. In this study, four different (5-20%) adaptation scenarios have been successfully integrated based on the CGE model to help the policymakers in deciding suitable policy options for climate change adaptation for the Malaysian food sector. Empirical examining of food sustainability and its adaptation policy, this study estimated that food sustainability concern with and without adaptation actions ranges from 5% to 20% from the baseline 2015 to 2065. However, this 5-20% adaptation cost scenarios have been calibrated in the model based on national accounts. All the values that are derived from the model calibration are based on monetary issues that are iv indicated in Malaysian Ringgit (RM). The results indicate that sustainable food production without adaptation options in the baseline is RM3.6 billion in 2015 which constitutes an approximate 30-35% shortage from the national targets and that shortage would increase to RM4.097 billion in 2065. Looking at sustainable food production, this study compared the cost-benefit of the application of adaptation costs from 2015 to 2065. According to this study‘s findings, the percentage in GDP for adaptation cost in 2015 is 0.00229, and the benefit is 0.0301; the percentage in GDP for adaptation cost in 2025 is 0.00229 and benefit is 0.0302; the percentage in GDP for adaptation cost in 2035 is 0.00229 and the benefit is 0.0324; the percentage in GDP for adaptation cost in 2045 is 0.00229 and benefit is 0.0303; the percentage in GDP for adaptation cost in 2055 is 0.00229 and benefit is 0.1280, and finally the percentage in GDP for adaptation cost in 2065 is 0.0024 and the benefit is 0.0305 with 5% adaptation action. Similar trends of benefit over cost ratio are found by other strategies such as by 10% and 15% adaptation actions over the study period, with the exception of 20%. Once the different levels of adaptation are considered, food sustainability shows a rising trend over time. The residual damage decreases with all adaptation actions in different scenarios. Although this study has incorporated four (4) different long term adaptation cost scenarios of climate change cost on the Malaysian food sector, it found that a 15% adaptation option based on national accounts might be the best policy option. Nevertheless, this study successfully proves that adaptation benefit exceeds the cost in any percentage of adaptation. This finding also indicates that there is no negative impact on the country‘s real GDP (RGDP) if suitable adaptation options are considered. Thus, the results justify prioritizing climate change adaptation for future food sustainability in Malaysia. The issues addressed in this study would be an applicable guideline for macroeconomic decision making with precise knowledge of the overall impacts of long v term adaptive measures. Finally, the suggested guidelines would enhance the current knowledge of setting up a long-term national adaptation policy.